Food stamp participation among adult-only households - David C. Ribar; Marilyn Edelhoch; Qiduan Liu (W.E. Upjohn Institute for Employment Research, 2009)
Several recent changes in the Food Stamp Program have been directed toward households without children. Some, including new work requirements for able-bodied adults without dependents (ABAWDs), were intended to promote self-sufficiency, while others, including easier application and recertification procedures, were intended to increase participation among underserved groups, such as the disabled and the elderly. Despite their relevance to policymakers, adult-only households have been examined by only a few studies. We use administrative records from South Carolina and event-history methods to investigate how spells of food stamp participation for adult-only households vary with ABAWD provisions, recertification intervals, economic conditions and other characteristics. We find that households that were subject to ABAWD policies had shorter spells and lower rates of food stamp participation than other households. We also find that households were much more likely to leave the Food Stamp Program at recertification dates than at other dates. Compared to married households, exit rates were lower for households in high unemployment areas, for female- and black-headed households, for individuals with less education, and for never-married households. We further find that the time limit was associated with exits with and without earnings, suggesting that this policy increased self-sufficiency for some households but left others without support.
Keywords: I3; J2; 330; food stamps; hazard models; time limits; recertification; Nahrungsmittelsubvention; Erwachsene; Privater Haushalt; USA; South Carolina